An in vitro comparison of four antibacterial agents with and without nicotine and their effects on human gingival fibroblasts. Issue 2 (7th January 2022) - Batra, Chandni; Alalshaikh, Marwa; Gregory, Richard L.; Windsor, L. Jack; Blanchard, Steven B.; Hamada, Yusuke
Abstract: Background: The purpose of the study was to compare anti‐bacterial activity of 0.12% chlorhexidine (CHX), 10% povidone iodine (PVD), Vega oral care gel (VEGA), and antioxidant gel (AO) on Streptococcus mutans, Streptococcus sanguis, Fusobacterium nucleatum, and Porphyromonas gingivalis with and without nicotine and to evaluate their effects on human gingival fibroblasts (HGFs). Methods: S. mutans, S. sanguis, P. gingivalis, and F. nucleatum were incubated with serial dilutions (1/4, 1/8, 1/16, 1/32, and 1/64) of anti‐bacterial agents in media (with and without nicotine). Minimum inhibitory and minimum bactericidal concentrations (MIC/MBC) were measured, and confocal microscopy was performed.  HGFs were exposed to serial dilutions (1/10, 1/100, 1/1000, and 1/10, 000) of antibacterial agents with media. Water‐soluble tetrazolium‐1 (WST‐1) assay and lactate dehydrogenase (LDH) assay were used to assess proliferation and cytotoxicity towards HGFs. Results: CHX and PVD significantly inhibited growth of all bacterial species ( P  < 0.0001) at all dilutions. AO and VEGA inhibited growth of all bacterial species up to only the 1/4 dilution. CHX and PVD decreased HGF proliferation at 1/10 and 1/100 dilution, whereas AO at all dilutions ( P  < 0.05). CHX and AO were cytotoxic at all dilutions ( P  < 0.05). VEGA was not cytotoxic to HGFs and did not affect HGF proliferation at any dilution ( P  > 0.05). An increased bacterial growth was seen for all species except P. gingivalis with addition of nicotine. Conclusion: CHX and PVD demonstrate superior antibacterial properties, but significantly reduce HGF proliferation. AO is bacteriostatic at lower dilutions but is highly toxic to HGFs. VEGA was bacteriostatic and demonstrated no detrimental effects on HGF's.